Survival analysis of the CEAwatch multicentre clustered randomized trial. Issue 8 (4th April 2017) - Verberne, C. J.; Zhan, Z.; van den Heuvel, E. R.; Oppers, F.; de Jong, A. M.; Grossmann, I.; Klaase, J. M.; de Bock, G. H.; Wiggers, T.
Abstract: Background: The CEAwatch randomized trial showed that follow‐up with intensive carcinoembryonic antigen (CEA) monitoring (CEAwatch protocol) was better than care as usual (CAU) for early postoperative detection of colorectal cancer recurrence. The aim of this study was to calculate overall survival (OS) and disease‐specific survival (DSS). Methods: For all patients with recurrence, OS and DSS were compared between patients detected by the CEAwatch protocol versus CAU, and by the method of detection of recurrence, using Cox regression models. Results: Some 238 patients with recurrence were analysed (7·5 per cent); a total of 108 recurrences were detected by CEA blood test, 64 (55·2 per cent) within the CEAwatch protocol and 44 (41·9 per cent) in the CAU group ( P  = 0·007). Only 16 recurrences (13·8 per cent) were detected by patient self‐report in the CEAwatch group, compared with 33 (31·4 per cent) in the CAU group. There was no significant improvement in either OS or DSS with the CEAwatch protocol compared with CAU: hazard ratio 0·73 (95 per cent 0·46 to 1·17) and 0·78 (0·48 to 1·28) respectively. There were no differences in survival when recurrence was detected by CT versus CEA measurement, but both of these methods yielded better survival outcomes than detection by patient self‐report. Conclusion: There was no direct survival benefit in favour of the intensive programme, but the CEAwatch protocol led to a higher proportion of recurrences being detected by CEA‐based blood test and reduced the number detected by patient self‐report. This is important because detection of recurrence by blood test was associated with significantly better survival than patient self‐report, indirectly supporting use of the CEAwatch protocol. Abstract : Intensive follow‐up no effect on survival